Effects of Cognitive Behavioral Therapy–Based Intervention on Improving Glycaemic, Psychological, and Physiological Outcomes in Adult Patients With Diabetes Mellitus: A Meta-Analysis of Randomized Controlled Trials - Yang, Xiangyun; Li, Zhanjiang; Sun, Jing (Frontiers in Psychiatry, 2020)
Background Patients with diabetes mellitus (DM) have a high risk of secondary physiological and psychological complications. Some interventions based on cognitive behavioural therapy (CBT) have been used to control glucose levels and improve negative emotions of patients with DM. This study was undertaken to provide an overview of the effectiveness of CBT-based interventions for improving glycaemic control, psychological and physiological outcomes in adult patients with DM. Methods Randomised controlled trials (RCTs) published in English and Chinese during 2007 and April 2019 were searched through various electronic databases including PubMed, Cochrane Library, Scopus, Embase, ProQuest Dissertations and Theses and the Chinese databases (WanFang data and China National Knowledge Infrastructure). The primary outcome variables included glycated haemoglobin (HbA1c), fasting plasma glucose (FPG), depression and anxiety symptoms. The secondary outcomes were weight and cholesterol. Effect sizes were pooled by random-effects modelling using Comprehensive Meta-Analysis software. Physiotherapy Evidence Database tool was used to assess the quality of all included studies. Results Twenty-three RCTs comprising 2619 patients with DM (type 1 and type 2) were included in at least one meta-analysis. The results of the main analysis showed that CBT-based interventions had a better effect on reduced HbA1c (−0.275%, 95% CI: −0.443 to −0.107; p < 0.01) with Hedge’s g of 0.466 (95% CI: 0.710 – 0.189), reduced depression symptoms with average reduction of −2.788 (95% CI: −4.450 to −1.207; p < 0.01) and Hedge’s g of 0.966 (95% CI: 1.507 – 0.426). Twenty-three RCTs comprising 2619 patients with DM (type 1 and type 2) were included in this meta-analysis. Several mediators of the effect were found through subgroup analysis for HbA1c and depression symptoms. The interventions emphasising completion homework assignments, stress management, and that used an interpersonal strategy delivered via a group had a better effect on both HbA1c and depression symptoms. Conclusions The findings indicate that CBT-based interventions are effective for improving glycaemic control and depression symptoms in adult patients with type 1 DM (T1DM) or type 2 DM (T2DM) with moderate to large effect size.